PERAN WAYANG SEBAGAI EKOLOGI BUDAYA TERHADAP CIPTA SASTRA SEJUMLAH SASTRAWAN INDONESIA MODERN - -, Wiyatmi (Diksi, 2015)
<img src="data:image/png;base64,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